Redesigning Driver’s License Application Processes for Motorcycle in Indonesia (SIM-C): An IT-Based Process Architectural Approach in The Effort of Shortening the Process Time - Irma Santikarama1, *Faiza Renaldi, Esmeralda C Djamal, Agya Java Maulidin (International Journal of Advanced Science and Technology, 2020)
Organizations nowadays constantly in search of brand-new management approachesto increase their competition related to rapid changes and technological developments.The same situation happens to government agencies in Indonesia, in this case, SATPASoffice which handles the application of a new driver’s license. When there was a leap ofmotorcycle ownership that happened in Indonesia during the last 20 years, the request fora motorcycle driver’s license or SIM-C has also increased dramatically. It is onlycommon to expect that chaos will come; long queues, long hours of waiting, uncleardocuments, are amongst the list of complaints that have happened when one person goesthrough the process of applying for SIM-C. This study attempts to minimize theprocessing time using Business Process Redesign (BPR). Many believes that successfulBPR can result in an enormous reduction in cost or cycle time. It can also potentiallycreate substantial improvement in quality, customer service, or other organizationalobjectives. The same situation and results have applied in this study. After using BPR withan architectural approach and gap analysis, we managed to shorten the processing timefrom 290 minutes or 4 hours 50 minutes to 228 minutes or 3 hours 48 minutes. There havebeen an 11.94%-time effectiveness within the activities, 42.70% within the buffer, andwith a total of 21.38% for the whole process of activities and buffers. Lastly, wevisualized all the suggested solutions using a wireframe of both web and mobile-based ITsystems to create a clear reference for further studies.